2018
DOI: 10.1074/jbc.m117.807214
|View full text |Cite
|
Sign up to set email alerts
|

A functional link between NAD+ homeostasis and N-terminal protein acetylation in Saccharomyces cerevisiae

Abstract: (Fig. 1D, upper panel).Similar to pnc1∆ mutant (Fig. 1B), both nat3∆and mdm20∆ released mostly NAM not NA (Fig.1D, lower panel). Fig. 1E (Fig. 2E, top panel) had a lesser effect (Fig. 2E, bottom (Fig. 3B). Next, we tested whether deleting ATG14 was sufficient to restore NAD + levels in the NatB mutants. As shown in Fig. 3C (left panel), deleting ATG14did not rescue the low NAD + levels in nat3∆ cells. Similarly, deleting other factors contributing to NR and NAM production ( Fig. 1A and Fig. 2E) in nat3∆ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(72 citation statements)
references
References 74 publications
7
65
0
Order By: Relevance
“…Interestingly, yeast NatB substrates are predominantly, near 100%, found in the acetylated state [28,29]. In line with these observations, we showed that Nma1 and Nma2 peptides identified from WT cells were 100% acetylated whereas Nma1 or Nma2 peptides identified from NatB mutants were 95%-100% non-acetylated [21]. Therefore, Nt-acetylation appears to be critical for maintaining proper Nmnat protein levels and thus NAD + biosynthesis.…”
Section: Introductionsupporting
confidence: 81%
See 4 more Smart Citations
“…Interestingly, yeast NatB substrates are predominantly, near 100%, found in the acetylated state [28,29]. In line with these observations, we showed that Nma1 and Nma2 peptides identified from WT cells were 100% acetylated whereas Nma1 or Nma2 peptides identified from NatB mutants were 95%-100% non-acetylated [21]. Therefore, Nt-acetylation appears to be critical for maintaining proper Nmnat protein levels and thus NAD + biosynthesis.…”
Section: Introductionsupporting
confidence: 81%
“…and Nma2 may be critical for the co-regulation of de novo, NA/NAM salvage and NR salvage pathways. In fact, we have previously shown that overexpression of NMA1 caused a significant increase in the total NAD + content of the cell [21]. It was also shown in a recent study that Nma1 is the only NAD + biosynthesis enzyme that upon overexpression can increase the NAD + content in the cell, and modulates NAD + to correlate with the concentrations of ATP [12].…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations